2022
DOI: 10.3389/fimmu.2022.977016
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of TIGIT in East Asian patients with solid cancers: A systematic review, meta-analysis and pancancer analysis

Abstract: BackgroundT-cell immunoreceptor with Ig and ITIM domains (TIGIT) participates in tumor immune escape by delivering inhibitory signals to T cells. The purpose of this article was to assess the prognostic value of TIGIT and its immunological function in solid cancers.MethodsThree databases were searched for relevant articles. The main endpoints were overall survival (OS), progression-free survival (PFS), recurrence-free survival (RFS), and disease-free survival (DFS). Hazard ratios (HR) were pooled by using fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Taking into account the immunosuppressive properties of TIGIT, high-level TIGIT expression generally indicates poor prognosis in solid tumors. A meta-analysis showed that high expression of TIGIT indicated worse overall survival (OS) [hazard ratio (HR) 1.73; 95% confidence interval (95% CI) 1.50–1.99], progression-free survival (PFS) (HR 1.53, 95% CI 1.25–1.88), recurrence-free survival (HR 2.40, 95% CI 1.97–2.93), and disease-free survival (HR 6.57, 95% CI 0.73–59.16) in East Asian patients with solid tumors [ 59 ]. A study revealed high expression of CD155 in murine and human pancreatic adenocarcinoma cells and showed that the activation of the TIGIT/CD155 axis was critical in immune evasion [ 60 ].…”
Section: The Central Role Of Tigit In the Cancer Immunotherapymentioning
confidence: 99%
“…Taking into account the immunosuppressive properties of TIGIT, high-level TIGIT expression generally indicates poor prognosis in solid tumors. A meta-analysis showed that high expression of TIGIT indicated worse overall survival (OS) [hazard ratio (HR) 1.73; 95% confidence interval (95% CI) 1.50–1.99], progression-free survival (PFS) (HR 1.53, 95% CI 1.25–1.88), recurrence-free survival (HR 2.40, 95% CI 1.97–2.93), and disease-free survival (HR 6.57, 95% CI 0.73–59.16) in East Asian patients with solid tumors [ 59 ]. A study revealed high expression of CD155 in murine and human pancreatic adenocarcinoma cells and showed that the activation of the TIGIT/CD155 axis was critical in immune evasion [ 60 ].…”
Section: The Central Role Of Tigit In the Cancer Immunotherapymentioning
confidence: 99%